2022
DOI: 10.3389/fvets.2022.913197
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Treatment- and Farm-Level Metrics of Antimicrobial Use Based on Used Daily Dose vs. Defined Daily Dose for the German Antibiotics Minimization Concept

Abstract: The German Antibiotics Minimization Concept defines a farm-level benchmarking process based on half-yearly treatment frequencies that applies to six animal populations for fattening: calves (≤ 8 months), cattle (> 8 months), piglets (≤ 30 kg), pigs (> 30 kg), broiler chickens, and turkeys. The treatment frequency defined in the Minimization Concept takes into account the number of animals treated, the treatment duration, and the number of active antimicrobial ingredients, for each individual trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Selective pressure of colistin on the intestinal microbiota could be high due to its lack of systemic resorption. In addition, colistin has been reported to often be greatly overdosed in poultry, as highly as 12-fold in chickens ( Bundesinstitut für Risikobewertung, 2022 ; Flor et al, 2022 ). However, at 66.2%, alarmingly high rates of mcr- Col-E were also found in herds that had not been treated with colistin at all.…”
Section: Discussionmentioning
confidence: 99%
“…Selective pressure of colistin on the intestinal microbiota could be high due to its lack of systemic resorption. In addition, colistin has been reported to often be greatly overdosed in poultry, as highly as 12-fold in chickens ( Bundesinstitut für Risikobewertung, 2022 ; Flor et al, 2022 ). However, at 66.2%, alarmingly high rates of mcr- Col-E were also found in herds that had not been treated with colistin at all.…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous alteration of the coding sequence that do not affect the protein function or the extensive use of colistin in poultry production in Germany may have been a driver for the evolution of the mcr-1 gene and eventually resulted in the emergence of mcr-1.26 ( 7 , 8 ). Colistin is generally administered to the entire flock for disease treatment or metaphylaxis purposes, which may have ensured the persistence of mcr-1.26 in poultry husbandry in Germany, thus providing a source for mcr-1.26 transmission into the food chain.…”
Section: Discussionmentioning
confidence: 99%
“…However, Germany still ranks 4th among countries in the European Union that sell the most colistin for food-producing animals ( 6 ). Calculations of antibiotic use in livestock production in Germany showed that colistin is frequently heavily overdosed especially in poultry husbandry, which may drive the emergence and transmission of colistin-resistant bacteria ( 7 , 8 ). The ever-increasing demand and large-scale production of retail meat are considered as drivers of resistant bacteria entering the food chain ( 9 ).…”
Section: Introductionmentioning
confidence: 99%